2018
DOI: 10.1084/jem.20180118
|View full text |Cite
|
Sign up to set email alerts
|

Irg1 expression in myeloid cells prevents immunopathology during M. tuberculosis infection

Abstract: Nair et al. define a key role for Irg1 in minimizing the pathological immune response associated with Mtb infection. Using Irg1−/− and Irg1fl/fl conditional mice, detailed immune cell analysis, and transcriptional profiling, their data supports a model where Irg1 expression in myeloid cell subsets tempers inflammation and controls the recruitment and infection of neutrophils during Mtb infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
222
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(256 citation statements)
references
References 21 publications
(39 reference statements)
20
222
0
Order By: Relevance
“…23 Their results demonstrated that the lungs from Irg1 À/À mice had increased percentages of infiltrated PMNs, indicating that Irg1 and its product itaconate function to limit inflammation by diminishing the accumulation of PMNs during M. tuberculosis infection. 23 Therefore, we hypothesized that the anti-inflammatory effects of DI treatment correlate with PMN infiltration. In this regard, our results show that treatment with DI effectively reduced MPO activity as well as PMN infiltration in infected corneas.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…23 Their results demonstrated that the lungs from Irg1 À/À mice had increased percentages of infiltrated PMNs, indicating that Irg1 and its product itaconate function to limit inflammation by diminishing the accumulation of PMNs during M. tuberculosis infection. 23 Therefore, we hypothesized that the anti-inflammatory effects of DI treatment correlate with PMN infiltration. In this regard, our results show that treatment with DI effectively reduced MPO activity as well as PMN infiltration in infected corneas.…”
Section: Discussionmentioning
confidence: 98%
“…tested the effect of Irg1 on the accumulation of PMNs in the lungs during M. tuberculosis infection . Their results demonstrated that the lungs from Irg1 −/− mice had increased percentages of infiltrated PMNs, indicating that Irg1 and its product itaconate function to limit inflammation by diminishing the accumulation of PMNs during M. tuberculosis infection . Therefore, we hypothesized that the anti‐inflammatory effects of DI treatment correlate with PMN infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of IRG1 also significantly inhibits LPS‐triggered production of TNF‐α, interleukin (IL)‐6 and interferon‐β in mouse macrophages . In contrast, knockout of IRG1 aggravates the inflammatory response in mouse bone marrow‐derived macrophages (BMDMs) challenged with LPS and myeloid cells infected with Mycobacterium tuberculosis . Furthermore, polymorphisms in the IRG1 gene are associated with the immune response to hepatitis B vaccination in the Chinese Han population …”
Section: Physiological Roles and Regulation Of Irg1mentioning
confidence: 99%
“…20 In contrast, knockout of IRG1 aggravates the inflammatory response in mouse bone marrow-derived macrophages (BMDMs) challenged with LPS 21 and myeloid cells infected with Mycobacterium tuberculosis. 22 Furthermore, polymorphisms in the IRG1 gene are associated with the immune response to hepatitis B vaccination in the Chinese Han population. 23 It has been reported that IRG1 is highly expressed in mouse macrophages in response to treatment with Tolllike receptor agonists 24 or infection with M. tuberculosis 25 or Chlamydia pneumoniae.…”
Section: Physiological Roles and Regulation Of Irg1mentioning
confidence: 99%
“…In turn, those activities are able to influence hostpathogen interactions, as it was shown in macrophages during Legionella pneumophila infection (Naujoks et al 2016;Price et al 2019). More recently, Nair et al showed that IRG1-deficient mice are highly susceptible to Mtb infection, while no aberrant phenotypes were found during influenza A virus or Listeria monocytogenes infection (Nair et al 2018). Their findings suggest that IRG1 expression in myeloid cells shape immunometabolic host responses by regulating neutrophil-dependent inflammation during Mtb infection of the lung.…”
Section: Introductionmentioning
confidence: 98%